The Travels of Pieter Albert Bik : Writings from the Dutch Colonial World of the Early Nineteenth Century - Bik, Pieter Albert, 1798-1855; Toivanen, Mikko (Colonial and global history through Dutch sources., 2017)
Pieter Albert Bik (1798-1855) was a Dutch colonial official whose work took him all over the world, including travels throughout Europe, the Dutch East Indies, and Japan. This book presents for the first time in English his autobiographical writings about those travels, which Bik never published in his lifetime. Presented here with annotations to set his observations in context, Bik's accounts offer a unique glimpse of the wide horizons of the world of Dutch colonialism in the first half of the nineteenth century, while editor Mikko Toivanen also draws interesting parallels between Bik's travels and the contemporary emergence of tourist travel in Europe.